Vision quest [videorecording (DVD)] - Ponicsan, Darryl; Peters, Jon; Guber, Peter; Becker, Harold; Modine, Matthew; Fiorentino, Linda; Schoeffling, Michael; Davis, Terry (Archive collection., 2011)
High school wrestler Louden Swain is a man obsessed, trying to shed 23 pounds in a dangerously short time and take on Shute, the undefeated, tough-as-nails 168-pound champion who's the best wrestler in the state.